PENGARUH CURRENT RATIO DAN EARNING PER SHARE TERHADAP DEBT TO EQUITY RATIO PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010-2014 - SURISMA YANTI (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2016)
This study aimed to determine how much influence the current ratio (CR) and earnings per share (EPS), affect the debt to equity ratio (DER). Multiple regression analysis using the 19 companies that were taken by purposive sampling in the Jakarta Stock Exchange observation period from 2010 through 2014. Analysis of the results of the regression performed after the model free from symptoms of classical assumption of multicollinearity, autocorrelation, and heteroscedasticity. Partial results of research found that the variables in the research model that is current ratio (CR) and earnings per share (EPS), which significantly affect the debt to equity ratio (DER). The coefficient of determination (R2), ie 52.6% indicate there are other factors that affect this analysis.Keywords: Current Ratio, Earning Per Share, Debt to Equity Ratio